2016
DOI: 10.1111/febs.13796
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding on biosensor tips: folding of maltodextrin glucosidase monitored by its interactions with GroEL

Abstract: Protein folding has been extensively studied for past four decades by employing solution based experiments such as solubility, enzymatic activity, secondary structure analysis, and analytical methods like FRET, NMR and HD exchange. However, for rapid analysis of the folding process, solution based approaches are often plagued with aggregation side reactions resulting in poor yields. In this work we demonstrate that a Bio-Layer Interferometry (BLI) chaperonin detection system can be potentially applied to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This would be consistent with the fact that the majority of GroES release was shown to occur via polarity change (69%) by way of a football complex (Yamamoto and Ando, 2016). Another reason for retaining such a cooperative system could be the fact that GroEL is able to fold large proteins that cannot be accommodated inside the cavity underneath the GroES (Chaudhuri et al, 2009; Dahiya and Chaudhuri, 2014; Pastor et al, 2016). In this instance, it is possible that release of the cis -bound substrate must be induced by trans binding of substrate, ATP and GroES in a fully alternating mechanism, although in this case, the folding protein would not have the benefit of encapsulation.…”
Section: Recent Developments and Outstanding Questionsmentioning
confidence: 99%
“…This would be consistent with the fact that the majority of GroES release was shown to occur via polarity change (69%) by way of a football complex (Yamamoto and Ando, 2016). Another reason for retaining such a cooperative system could be the fact that GroEL is able to fold large proteins that cannot be accommodated inside the cavity underneath the GroES (Chaudhuri et al, 2009; Dahiya and Chaudhuri, 2014; Pastor et al, 2016). In this instance, it is possible that release of the cis -bound substrate must be induced by trans binding of substrate, ATP and GroES in a fully alternating mechanism, although in this case, the folding protein would not have the benefit of encapsulation.…”
Section: Recent Developments and Outstanding Questionsmentioning
confidence: 99%
“…To optimize the refolding of mutant R52Tat without EGFP, we compared the effect of an uncrowded environment on the TatR52A (purified) in E. coli cells with that of a crowded environment on EGFP in the absence of TAR RNA by BLI at 1.3 nm during a refolding period of 20 min ( Figures S4 and S5 ) [ 56 ]. We used this well-characterized system to assess the response of His-tagged Tat-BLI after binding to the TAR RNA substrate to design a BLI-detection study for mutant R52Tat folding without EGFP in the absence of TAR RNA ( Figure 5 and Figure S4 ) [ 3 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fold changes for each mutant compared with the WT values were calculated. The BLI experiments were performed using the general BLI analysis protocol, as described previously [ 56 ]. Data analysis, including double reference subtraction, was performed with the ForteBio data analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…Separate control experiments indicated the immobilized MalZ, which was completely denatured at high urea concentrations at 25 °C, refolds very slowly (t 1/2 at 25 °C of ∼10 min) relative to the wash times that were used to remove an adhering denaturant or a ligand solution. 36 It was also shown that the refolded MalZ immobilized on and released from Ni-NTA surfaces was functionally active with yields that were substantially improved compared to those of solution refolding. 36 These control measurements indicated that no substantial refolding was detected (i.e., chaperonin binding amplitudes remain high) if two separate MalZ attached tips were compared before and after a 10 s wash period.…”
Section: ■ Resultsmentioning
confidence: 99%